Sustentabilidade corporativa em seguros : proposta e teste de um modelo integrado - Nogueira, Flávio Geraldo (2018)
The aim of this study is to understand the relationships between the underwriting of environmental, social and governance risks (ESG) and the operational management of these issues in the insurance industry in Brazil. To achieve this goal, a framework was developed to assess the underwriting of these emerging risks and their incorporation in the operational management of insurance companies, as well as proposed and tested an integrated model of the relationships between these issues. The methodology used a survey with industry professionals. The main data analysis methods applied exploratory and confirmatory factor analysis and structural equations modeling. The results indicate that the insurance industry in Brazil offers few coverages for ASG risks, particularly for climate change risks. Gaps identified between the recognition of materiality and the offer of insurance coverage, mainly in relation to environmental liability risks related to the ecosystems degradation and specific health coverage for emerging manmade risks, indicate product development opportunities. The integrated model indicated that the industry incorporates sustainability issues in business mainly due to the size of the companies and the internal management of environmental issues. Based on the results obtained, recommendations are presented to promote the development of new products and more robust metrics of the progress of sustainability in the Insurance industry.